“The Simpler, the Better.” A Qualitative Study on Digital Health Transformation in Early Adopter Rheumatology Outpatient Clinics - May, Susann; Darkow, Robert; Knitza, Johannes; Boy, Katharina; Schwarz, Julian; Heinze, Martin; Hornig, Johannes; Aries, Peer; Welcker, Martin; Muehlensiepen, Felix (Inquiry-The Journal of Health Care Organization Provision and Financing, 2024)
Workforce shortage and the increasing burden of rheumatic and musculoskeletal diseases lead to extreme time constraints in rheumatology outpatient care. Digital services promise to facilitate care by relieving employees and unleash new capacities. This study aims to explore the perspectives of early adopter health care professionals (HCP) on digital transformation in outpatient rheumatology. In-depth qualitative interviews were conducted with rheumatology nurses and physicians in 3 German rheumatology outpatient clinics, each characterized by an advanced level of digital adaption. Qualitative data were subsequently analyzed using deductive-inductive qualitative content analysis. Interviews with 11 rheumatology nurses and 5 rheumatologists were completed. Three key themes emerged from the qualitative analysis: (i) Digital transformation of care; (ii) impact of digital transformation on health care delivery; and (iii) perceived drivers of successful digitalization. The interviews revealed that digital technologies are widely used throughout the complete patient pathway. Digitalization enables more continuity and flexibility in rheumatology care. Patient information can be electronically obtained in a standardized manner prior to planned visits, enabling an informed consultation and more time for in-depth patient discussion. Although digitalization restructures work, it can also increase the current workload. Improved accessibility for patient calls leads to more work for HCP. Important drivers of successful digital technology implementation are low-threshold and interoperable services, a medical team that is interested and educated in eHealth, and comprehensive patient information and onboarding. Digital transformation is increasingly redefining rheumatology care. While accelerating communication and workflows, improved service accessibility leads to more work for HCP.
CRIS-Team Scopus Importer:2024-06-07
Keywords: digital health; health services research; implementation research; qualitative research; rheumatology; telemedicine